Protection System on Connect Panel for Use 7KT Smart Multi Function Meter Based on PLC and HMI via Modbus RTU Communication - Triyono, Budi; Nur, Dimas; Winarno, Basuki; Prasetyo, Yuli (International Journal of Multidisciplinary Approach Research and Science, 2024)
One function of the protection system is to avoid or reduce damage to electrical equipment due to abnormal conditions such as undervoltage, overvoltage, overcurrent, underfrequency and harmonics. This protection system requires a Smart 7KT Multi-Function Meter and a PLC. Where the Smart 7KT Multi-Function Meter is used for monitoring then transferred to the PLC and detecting any abnormalities in the system when a disturbance occurs then the Smart 7KT Multi-Function Meter will send data to the PLC, then send a signal to the circuit breaker to disconnect the network that is experiencing disturbance. While the PLC is used to execute data that has been taken by the Multi-function Meter Smart 7KT for control or control on the Multi-function Meter Smart 7KT. When a disturbance occurs, the program on the PLC will protect and the type of disturbance will be displayed on the HMI screen. The results of this project were successful in securing undervoltage disturbances of 314.2 V for line voltages, overvoltage of 412.1 V for line voltages, overcurrent of 1.6 A, and testing of THD voltage between phases V12 of 1.3%, THD V23 of 1.1%, and THD V13 of 1.1%, for THD currents of 14.6% for THD I1, THD I2 of 9.4%, and THD I3 of 10.6% which occur in the electric power installation network which causes damage to electrical equipment.